Public information campaigns & opinion research : a handbook for the student & practitioner - Klingemann, Hans-Dieter; Römmele, Andrea, 1967- (SAGE, 2002)
Based upon the experiences of campaign practitioners and multidisciplinary insights, this handbook explains how to plan implement and measure public opinion using survey research and market research tools.